Impact of extensive surgery in multidisciplinary approach of pterygopalatine/infratemporal fossa soft tissue sarcoma1. Issue 6 (9th January 2013) - Minard‐Colin, Véronique; Kolb, Frédéric; Saint‐Rose, Christian; Fayard, Florence; Janot, François; Rey, Annie; Canale, Sandra; Julieron, Morbize; Corradini, Nadège; Raquin, Marie‐Anne; Habrand, Jean‐Louis; Grill, Jacques; et al.
Abstract Background To evaluate a strategy whereby extensive surgery ± external radiotherapy (RT) could improve local control in pterygopalatine/infratemporal fossa (PIF) sarcoma. Procedure Forty‐one patients with a diagnosis of sarcoma involving the PIF and referred to our Institute from 1984 to 2009 were included in the analysis. Patients received multidrug chemotherapy and radiotherapy ± surgery, depending on the period of treatment. Results The median age at diagnosis was 7.6 years (range: 0.1–22 years). There were 36 RMS, 3 undifferentiated sarcoma and 2 other soft‐tissue sarcomas. Sixty‐eight percent of patients had meningeal risk factors at diagnosis. Local treatment consisted of RT alone in 19 patients, surgery in combination to RT in 19 patients and surgery alone in 3 patients. The local progression rate (LPR) at 5 years was 45% for the entire population, 59% for the 19 patients treated with RT alone and 34% for the 22 patients who had surgery as part of their treatment. All locoregional failures after extensive surgery occurred at the skull base and/or in leptomeningeal spaces. Conclusions Multidisciplinary approach including extensive surgery for PIF sarcoma is feasible and yields good local control with 15/22 patients in local complete remission. Future studies are warranted to confirm these promising results, to evaluate the possibility of avoiding RT or limiting the RT field, and to extend the indication for extensive surgery to other "worse" sites of PM sarcoma such as the paranasal sinuses. Pediatr Blood Cancer 2013; 60: 928–934. © 2013 Wiley Periodicals, Inc.